Review: - Louie Giray (Culturales)
Billie Eilish, a young yet famous American singer-songwriter, had been trending online because of her conversations with a radio host. At the age of 11, she confessed she first started watching pornography, which gradually made a negative impact on her life. She narrated, “I think it [pornography] really destroyed my brain and I feel incredibly devastated that I was exposed to so much porn” (Eilish, as stated in Nicholson, 2021). Eilish is only one of the many who are secretly suffering from being addicted to pornography. Indeed, this has sparked a critical conversation about porn which many just shy away.